Influence of Fractal Surface Parameters on the Elasto-Plastic Contact Behavior of Rough Surfaces - Willner, Kai (Journal of Tribology, 2008)
In a recent paper (2004, "Elasto-Plastic Normal Contact of Three-Dimensional Fractal Surfaces Using Halfspace Theory," J. Tribol., 126, pp. 28-33) the author developed a halfspace model for the elasto-plastic normal contact of rough surfaces. This model is now used to study the inuence of intrinsic surface pa-rameters on constitutive contact laws, such as load-gap relation and load-area relation, for a specic type of surface topography known as fractal-regular surfaces. Numerical investigations show that the fractal dimension has only minor inuence on the load-gap relationship, which is mostly determined by the dimensionless ratio between the transition length and the rms values of the height data. Due to the fractal nature of the surfaces at the small wavelength limit, initial deformation will always be in the plastic range. The load-area relation becomes then completely independent of the geometric surface parameters and is determined by material properties alone, at least if the predicted plastic defor-mation occurs at a length scale larger than the atomic scale. © 2008 by ASME.
UnivIS-Import:2015-03-09:Pub.2008.tech.FT.FT-TM.influe_1
Keywords: Elasto-plastic contact; Fractal-regular surface; Halfspace theory